Long‐term influence of early human occupations on current forests of the Guiana Shield. Issue 10 (24th July 2019) - Odonne, Guillaume; van den Bel, Martijn; Burst, Maxime; Brunaux, Olivier; Bruno, Miléna; Dambrine, Etienne; Davy, Damien; Desprez, Mathilde; Engel, Julien; Ferry, Bruno; Freycon, Vincent; Grenand, Pierre; et al.
Abstract: To decipher the long‐term influences of pre‐Columbian land occupations on contemporary forest structure, diversity, and functioning in Amazonia, most of the previous research focused on the alluvial plains of the major rivers of the Amazon basin. Terra firme, that is, nonflooded forests, particularly from the Guiana Shield, are yet to be explored. In this study, we aim to give new insights into the subtle traces of pre‐Columbian influences on present‐day forests given the archaeological context of terra firme forests of the Guiana Shield. Following archaeological prospects on 13 sites in French Guiana, we carried out forest inventories inside and outside archaeological sites and assessed the potential pre‐Columbian use of the sampled tree species using an original ethnobotanical database of the Guiana Shield region. Aboveground biomass (320 and 380 T/ha, respectively), basal area (25–30 and 30–35 m 2 /ha, respectively), and tree density (550 and 700 stem/ha, respectively) were all significantly lower on anthropized plots (As) than on nonanthropized plots (NAs). Ancient human presence shaped the species composition of the sampled forests with Arecaceae, Burseraceae, and Lauraceae significantly more frequent in As and Annonaceae and Lecythidaceae more frequent in NAs. Although alpha diversity was not different between As and NAs, the presence of pre‐Columbian sites enhances significantly the forest beta diversity at the landscape level. Finally, trees with edible fruits are positively associated with pre‐Columbian sites, whereas trees used for construction or for their bark are negatively associated with pre‐Columbian sites. Half a millennium after their abandonment, former occupied places from the inner Guiana Shield still bear noticeable differences with nonanthropized places. Considering the lack of data concerning archaeology of terra firme Amazonian forests, our results suggest that pre‐Columbian influences on the structure (lower current biomass), diversity (higher beta diversity), and composition (linked to the past human tree uses) of current Amazonian forests might be more important than previously thought.